Graphs of protein-water hydrogen bond networks to dissect structural movies of ion-transfer microbial rhodopsins - Bertalan, Éva; Bondar, Ana-Nicoleta (Frontiers in Chemistry, 2023)
Microbial rhodopsins are membrane proteins that use the energy absorbed by the covalently bound retinal chromophore to initiate reaction cycles resulting in ion transport or signal transduction. Thousands of distinct microbial rhodopsins are known and, for many rhodopsins, three-dimensional structures have been solved with structural biology, including as entire sets of structures solved with serial femtosecond crystallography. This sets the stage for comprehensive studies of large datasets of static protein structures to dissect structural elements that provide functional specificity to the various microbial rhodopsins. A challenge, however, is how to analyze efficiently intra-molecular interactions based on large datasets of static protein structures. Our perspective discusses the usefulness of graph-based approaches to dissect structural movies of microbial rhodopsins solved with time-resolved crystallography.